Commentary for "Examining the use of 'parental alienation syndrome'". Issue 2 (2nd July 2016) - Shaw, Morgan
ABSTRACT: This commentary is in response to the article, "Examining the use of 'parental alienation syndrome, '" and provides useful information to individuals and institutions within both the mental health and legal fields. Further exploration of the concepts within Richard Gardner's parental alienation syndrome (PAS) is important given the fact that PAS has no methodologically sound, peer-reviewed research and yet legal systems and mental health professionals continue to rely on it greatly in making very important legal decisions that affect the lives of many. While attorneys, judges, or clinicians may not say a child is suffering from PAS, or may never even use the term "alienating, " they still base their opinions and subsequent recommendations on Gardner's concepts and ideology. Articles like this one hopefully bring light to these important areas and bring the focus back on what is in the best interest of the children.